Bank Financing Of Algerian Smes: Approach By Survey Of Banks In The Wilaya Of Bejaia - Saidani, Salim; Mouffok, Nacer-eddine (جامعة الوادي - University of Eloued, 2021)
This paper aims to assess the possible link between SMEs and banks in the wilaya of Bejaia, by highlighting the needs, conditions and methods of financing this category of businesses. For this, we used two approaches. First, a field survey of the sixteen banks in the wilaya of Bejaia. Then, an econometric modeling based on the LOGIT model. The data is processed by two software: Sphinx IQ and SPSS. The results obtained confirm the fact that Algerian banking regulations, associated with the long and complex procedural scheme of credit institutions towards SMEs, lead these banks to be more wary of companies, by demanding more guarantees.
مقال
Keywords: Bank ; credit ; financing ; guarantees ; SMEs